Monitoring of prolactin levels in children and adolescents prescribed antipsychotic medication: a complete audit cycle. (15th March 2016) - Uduehi, E.; Gallagher, L.; Alugo, T.
Abstract : Aims and methods: Antipsychotics have proven benefits in children and adolescents with autism spectrum disorders. However, notwithstanding some therapeutic benefits significant side effects are associated with the use of antipsychotics, such as hyperprolactinaemia. We completed an audit cycle between April 2013 and December 2013 to evaluate the practice in the Beechpark Autism Service with respect to monitoring and managing hyperprolactinaemia in children and adolescents prescribed antipsychotics. The re-audit assessed whether the recommended guidelines and changes had been implemented. The National Institute for Health and Care Excellence guidelines were used as a gold standard for this audit. Results: Basal determinations of serum prolactin improved significantly at the end of the audit cycle (28.6% v . 57%) with slight improvement in six monthly repeat prolactin monitoring (28.6% v . 39.1%) showing some change in clinical practice. However, there was minimal improvement in managing hyperprolactinaemia (0% v . 12.5%). Clinical implication: There is growing awareness about hyperprolactinaemia associated with the use of antipsychotic medication in children and adolescents and the long-term effects. Clear documented guidelines will help increase and improve the monitoring and management of hyperprolactinaemia in these groups of patients. However, more needs to be done in improving the practice of monitoring and managing hyperprolactinaemia in children and adolescent prescribed antipsychotic medication giving the documented long-term effects.